Effects of Mutations in the Pseudomonas putida miaA Gene: Regulation of the trpE and trpGDC Operons in P. putida by Attenuation - Olekhnovich, Igor (American Society for Microbiology, 2001)
Tn5 insertion mutants defective in regulation of the Pseudomonas putida trpE and trpGDC operons by tryptophan were found to contain insertions in the P. putida miaA gene, whose product (in Escherichia coli) modifies tRNA(Trp) and is required for attenuation. Nucleotide sequences upstream of trpE and trpG encode putative leader peptides similar in sequence to leader peptides found in other bacterial species, and the phenotypes of the mutants strongly suggest that transcription of these operons is regulated solely by attenuation.